Mitochondrial genome of Murina shuipuensis (Chiroptera: Vespertilionidae) from Shuifu Village, Guizhou, China (type locality) - Zhenglanyi Huang; Yang Yue; Sanjan Thapa; Yifeng Hu; Yi Wu; Wenhua Yu (Mitochondrial DNA. Part B. Resources, 2019)
Murina shuipuensis, a small-sized forest bat with distinct bright orange-yellow ventral fur, is only found from its type locality thus far. In this study, a complete mitochondrial genome of a male individual of M. shuipuensis from Shuifu Village, Libo, Guizhou China (type locality) was sequenced using Illumina Hiseq. Total length of its genome is 16,585 bp, including two rRNA genes, 22 tRNA genes, 13 protein-coding genes, and a control region. The general arrangement of genes is similar to the other chiropteran mitochondrial genomes. The phylogenetic inference indicates M. shuipuensis and M. leucogaster have closer phylogenetic relationship than other taxa that deposited in NCBI-nt. The complete mitochondrial genome provides valuable information for further taxonomic and phylogenetic researches.